Magnetic,structural and electrical properties of aluminium-substituted Yttrium iron garnet (Y₃Fe₅- AlᵪO₁₂ with X=0, .., 3.0) prepared via auto-combustion sol-gel method - Abdullahi, Musa Makiyyu (2016)
YIG ferrite material has been attracting attention due to its high electric resistivity, high radiation stability, comparatively low magnetization, narrowest ferromagnetic line width and consequent low loss. In this work, aluminum-substituted Yttrium iron garnet, (Y3Fe5-xAlxO12) powders, with x = 0, 0.2, 0.4, 0.6, to 3.0 were prepared using auto-combustion sol-gel method. The structural, magnetic and dielectric properties, at radio frequency range, were studied so as to contribute towards the study and improvement of microwave communication materials. The X-ray diffraction (XRD) revealed the most representative peaks for YIG structure (400), (420) and (422) sharply reflected as matched by ICSD data. However, single garnet phase was found to be limited to 0.6 ≤ x ≤ 1.6. The morphology of the samples, studied by Field Emission Scanning Electron Microscope (FESEM) shows decreasing grain sizes as Al concentration increases. Magnetic properties of the samples were studied using vibrating sample magnetometer (VSM). Saturation magnetization, Ms was observed to decrease from 20.721 emu/g to 0.8112 emu/g as x increases from 0 to 3.0, while remnance magnetization, Mr decreased from 2.23 emu/g at x = 0, to 0 emu/g at x = 1.8 and above. The Coercivity, Hc changed non-linearly with x, having a maximum value of 39.00 Oe at x = 0.8 and a minimum value of 0 Oe at x ≥ 1.8. Dielectric properties of the samples were obtained at room temperature using Agilent impedance analyzer. At 1 MHz, the dielectric constant, εr of the samples decreases from its maximum value of 36.911 at x = 0 to its minimum value of 5.63 at x = 0.6. Dielectric loss tangent, tan δ has a minimum value of 0.016 at x = 3.0 and a maximum value of 0.184, while the pure sample has a value of 0.027 at 1 MHz. The conductivity decreased from 5.902 x 10-5 Sm-1 at x = 0 to its minimum value of 4.5 x 10-6 for x = 0.4, and increased thereafter, while the resistivity shows a reversed trend. The magnetic permeability, μ shows a decreasing trend increasing frequency. At 1 MHz, the value increased from 26.75 at x = 0 to 1263.12 at x = 0.4, while magnetic loss tangent, tan μ decreased from 0.029 to 0.0096 as x increases from 0 to 0.4. From the result, it shows that the Al-YIG materials have good magnetic and dielectric properties, μr > 1, εr > 1, tan δ < 1and tan μ < 1. This is suitable for antenna miniaturization that can enhance the performance of radio wave communication devices.